Study of Testis Volume Density and Relative Weight of Tissue Components in Different Ages for Local Bulls in Sulaimani Province - Omar, Chowman Aladdin (Journal of Kerbala for Agricultural Sciences, 2018)
The present study is carried out to investigate the reproductive activity of mature Local bull and effect of age’s changes on the testes activity by using Testis Volume Density (VD %) and Relative Weight (RW, gbody weight) of Tissue Components. Seventy-two testes of the bull were taken from the Sulaimani slaughterhouse in November 2016. The length and width of the right testis were measured after slaughtering, and testes weights were also taken, then the epididymis carefully dissected. The diameters of testicular seminiferous tubules were also measured. The present study demonstrated a significant increased (p<0.05) in weight (221.5±6.4gm), length (15.00±0.57cm), width (6.33±0.33cm) and testes circumference (19.00±0.01cm) in age 4th-year-old compared to other ages. The diameter of epididymis (p<0.05) increased significantly in 2nd, 3rd and 4th age old for total length and head of epididymis (Caput) compared to 1st-year. The diameter of the seminiferous tubules demonstrated higher (p<0.05) significant in thickness of seminiferous tubules demonstrated higher significance in 4th ages. The increase in spermatogenesis process leads to increase the diameter and thickness of seminiferous. The results showed that the degenerative changes in germ cells are associated with histomorphometric variations, including the density of the structures that comprise the testicular parenchyma, and are they representative in bulls with poor semen quality at an early age. In addition, the unsatisfactory bulls for reproduction showed reduced meiotic potential at 1st-year compared to that of satisfactory reproductive bulls, especially at 3 and 4 years old.